2010
DOI: 10.1007/s10484-010-9141-y
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability (HRV) and Posttraumatic Stress Disorder (PTSD): A Pilot Study

Abstract: Exposure to combat experiences is associated with increased risk of developing Post Traumatic Stress Disorder. Prolonged exposure therapy and cognitive processing therapy have garnered a significant amount of empirical support for PTSD treatment; however, they are not universally effective with some patients continuing to struggle with residual PTSD symptoms. Heart rate variability (HRV) is a measure of the autonomic nervous system functioning and reflects an individual's ability to adaptively cope with stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
154
2
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(183 citation statements)
references
References 35 publications
10
154
2
6
Order By: Relevance
“…Significant correlations have been reported between the cardiac rate and resting BOLD signal time courses, particularly negative correlations in gray matter (Chang et al, 2009). Thus, possible differences in heart rate variability associated with PTSD (Tan et al, 2011) might confound the present results. Our approach conceptualized amygdala complexes as seeds and cortical regions as targets.…”
Section: Limitationsmentioning
confidence: 68%
“…Significant correlations have been reported between the cardiac rate and resting BOLD signal time courses, particularly negative correlations in gray matter (Chang et al, 2009). Thus, possible differences in heart rate variability associated with PTSD (Tan et al, 2011) might confound the present results. Our approach conceptualized amygdala complexes as seeds and cortical regions as targets.…”
Section: Limitationsmentioning
confidence: 68%
“…They found that the SDNN was lower in this group compared with available norms, though only for all three conditions in combination. Tan, Dao, Farmer, Sutherland, and Gevirtz (2011) found that SDANN was significantly lower for the group of veterans with PTSD compared to control subjects, with a large effect size. The researchers further examined an HRV biofeedback paradigm, providing half of the PTSD group with eight HRV biofeedback sessions in addition to their ongoing treatment.…”
Section: Positive Tb Skin Test Tuberculosismentioning
confidence: 88%
“…Studies have also shown that HRV biofeedback treatment can provide significant relief for individuals with combat related PTSD (Tan, Dao, Farmer, Sutherland, & Gevirtz, 2011;Zucker et al, 2009). Individuals with PTSD are able to alleviate symptoms (e.g., hyperarousal) through HRV biofeedback training, by controlling and maintaining their respiration at resonant frequency.…”
Section: Frequency Analysesmentioning
confidence: 99%
“…Clients undergoing heart rate variability training are asked to first meet with the therapist to determine what breathing rate will produce their greatest heart rate variability (Lehrer et. al., 2000;Tan et. al., 2011).…”
Section: Heart Rate Variability Biofeedback Trainingmentioning
confidence: 99%